An Optimized IWT–DCT Watermarking Scheme Based on Multiple Matrix Decomposition and MOWOA2 - Wei, Deyun; Deng, Yang (Circuits, systems, and signal processing, 2024)
In this paper, we propose a mixed-domain watermarking algorithm based on integer wavelet transform (IWT), discrete cosine transform (DCT) and multiple matrix decomposition. The combination of IWT–DCT avoids the rounding error of discrete wavelet transform (DWT) in the existing algorithm, so it has better performance than the combination of DWT–DCT. Singular value decomposition (SVD) based watermarking algorithm has a false positive problem (FPP), despite its strong robustness. To solve FPP, we propose a scheme based on two-stage encryption and multi-decomposition. This scheme also further improves the security of the algorithm. In addition, we double embed the watermark data into the host image, and introduce improved multi-objective whale optimization algorithm (MOWOA2) to optimize the embedding intensity of different frequency sub-bands. It not only avoids the problem of weight selection in the face of multiple fitness functions, but it strengthens the algorithm's resistance to various attacks. In comparison to other relevant algorithms, simulation findings demonstrate that the proposed approach has good security, invisibility, and robustness, particularly in resisting various clipping attacks and flipping assaults.